2019
DOI: 10.3389/fonc.2019.00512
|View full text |Cite
|
Sign up to set email alerts
|

The Melding of Drug Screening Platforms for Melanoma

Abstract: The global incidence of cancer is rising rapidly and continues to be one of the leading causes of death in the world. Melanoma deserves special attention since it represents one of the fastest growing types of cancer, with advanced metastatic forms presenting high mortality rates due to the development of drug resistance. The aim of this review is to evaluate how the screening of drugs and compounds for melanoma has been performed over the last seven decades. Thus, we performed literature searches to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 164 publications
(165 reference statements)
0
20
0
Order By: Relevance
“…HaCaT cells were chosen as the nonmalignant control due to their ease of propagation, near normal phenotype and general use as an A375 control (Dwivedi et al, 2015;Lewies et al, 2018). The A375 cell line is a melanotic cells line with the BRAF mutation frequently used for in vitro drug screening assays for anti-melanoma drugs (Couto et al, 2019). All reagents were of analytical grade and were obtained from Merck (Darmstadt, Germany) unless stated otherwise.…”
Section: Cell Culturesmentioning
confidence: 99%
“…HaCaT cells were chosen as the nonmalignant control due to their ease of propagation, near normal phenotype and general use as an A375 control (Dwivedi et al, 2015;Lewies et al, 2018). The A375 cell line is a melanotic cells line with the BRAF mutation frequently used for in vitro drug screening assays for anti-melanoma drugs (Couto et al, 2019). All reagents were of analytical grade and were obtained from Merck (Darmstadt, Germany) unless stated otherwise.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Numerous high-throughput genomic and proteomic studies comparing healthy and cancerous cells have identified many such potential drug targets [9,12,13]. These putative targets are then subjected to high-throughput screening with libraries of potential drug candidates, such as peptides, antibodies, natural compounds, chemicals, and aptamers [10,[14][15][16][17][18][19][20][21][22]. Selected molecules that specifically bind to the target are considered for further functional validation [17].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that VWCE may activate or inhibit immune cells infiltrating the tumor, although the underlying mechanism involved is unknown. Macrophages are a group of differentiated immune cells and classify as M1 macrophages and M2 macrophages [ 47 ]. They play an important role in development, homeostasis, and immunity [ 48 ].…”
Section: Discussionmentioning
confidence: 99%